The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1148/radiol.2018171531
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Hypoxia in Renal Carcinoma with Oxygen-enhanced MRI: Comparison with Intrinsic Susceptibility MRI and Pathology

Abstract: PurposeTo cross-validate T1-weighted oxygen-enhanced (OE) MRI measurements of tumor hypoxia with intrinsic susceptibility MRI measurements and to demonstrate the feasibility of translation of the technique for patients.Materials and MethodsPreclinical studies in nine 786–0-R renal cell carcinoma (RCC) xenografts and prospective clinical studies in eight patients with RCC were performed. Longitudinal relaxation rate changes (∆R1) after 100% oxygen inhalation were quantified, reflecting the paramagnetic effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Using an IAUGC 60 map from DCE‐MRI as a mask to obtain Oxy‐R fractions O’Connor et al showed good correlation with the histological hypoxic fraction . In more recent work, Little et al showed oxygen enhancement in tumors with a histological hypoxic fraction as high as 43% and this translated very well to a study of six renal cell carcinoma patients. Linnik et al reported excellent correlation between percentage of “negative AUC OE ” ( O 2 ‐negative) voxels and percentage of hypoxic areas in the highly vascular preclinical U87MG tumor xenografts .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Using an IAUGC 60 map from DCE‐MRI as a mask to obtain Oxy‐R fractions O’Connor et al showed good correlation with the histological hypoxic fraction . In more recent work, Little et al showed oxygen enhancement in tumors with a histological hypoxic fraction as high as 43% and this translated very well to a study of six renal cell carcinoma patients. Linnik et al reported excellent correlation between percentage of “negative AUC OE ” ( O 2 ‐negative) voxels and percentage of hypoxic areas in the highly vascular preclinical U87MG tumor xenografts .…”
Section: Discussionmentioning
confidence: 91%
“…Linnik et al reported excellent correlation between percentage of “negative AUC OE ” ( O 2 ‐negative) voxels and percentage of hypoxic areas in the highly vascular preclinical U87MG tumor xenografts . A second approach for differentiating between viable but hypoxic regions and unperfused dead tissues, is to combine OE‐MRI with T2* W acquisition and the BOLD effect to classify regions that show both effects. Excess oxygen in the blood will induce changes in Hb saturation, which alter the T2* resulting in a robust measure of areas with functioning vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotic regions have been identified using diffusion methods (ADC and IVIM) based on the intrinsic tissue water properties or DCE MRI based on the intravenous infusion of gadolinium contrast agents . BOLD contrast has been compared to the non‐model‐based DCE parameters and showed similar capability of imaging vasculature and revealing intratumoral heterogeneity .…”
Section: Discussionmentioning
confidence: 99%
“…Necrotic regions have been identified using diffusion methods (ADC and IVIM) based on the intrinsic tissue water properties 66,67 or DCE MRI based on the intravenous infusion of gadolinium contrast agents. 8,68,69 BOLD contrast has been compared to the non-model-based DCE parameters and showed similar capability of imaging vasculature 48 and revealing intratumoral heterogeneity. 63,70 Potential advantages of using BOLD response to classify intratumoral heterogeneity include: 1) BOLD response relates directly to tumor oxygenation 36 ; 2) BOLD measurements can be interleaved with TOLD measurements for a single gas breathing intervention, avoiding the need for an additional scanning sequence such as DCE or IVIM; 3) avoiding the need for exogenous gadolinium contrast agents, which have become controversial for routine use.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor hypoxia is a well-established cause of treatment resistance, adversely affects the prognosis of HNSCC ( 21 , 22 ), and moderates the expression and activation of EGFR ( 26 ). Both intrinsic susceptibility and oxygen-enhanced MRI are being actively exploited for spatially mapping tumor hypoxia in vivo ( 36 , 45 , 48 50 ). Oxygen inhalation induced a reduction in of both CAL R and CAL S xenografts, a consequence of a reduction in paramagnetic deoxyhaemoglobin in perfused tumor blood vessels.…”
Section: Discussionmentioning
confidence: 99%